The effects of pregnancy in subjects with repaired tetralogy of Fallot - Duarte, Valeria E.; Yamamura, Kenichiro; Economy, Katherine E.; Graf, Julia A.; Lu, Minmin; Assenza, Gabriele Egidy; Karur, Gauri R.; Marenco, Anais; Ishikita, Ayako; Duncan, Madeline E.; Geva, Tal; Wald, Rachel M.; et al. (The American heart journal, 2024)
Previous reports reveal inconsistent findings of right ventricular (RV) changes following pregnancy in subjects with repaired tetralogy of Fallot (rTOF). A two-center, retrospective cohort study which included women with rTOF who completed pregnancy that were matched to nulliparous women with rTOF by age at the time of baseline cardiac magnetic resonance (CMR), RV ejection fraction (RVEF), and indexed RV end-diastolic volume (RVEDVi). Pre-pregnancy and postpartum cardiac magnetic resonance (CMR) were analyzed and compared to sequential CMR of nulliparous subjects with rTOF. Thirty-six women with rTOF who completed pregnancy were matched to 72 nulliparous women with rTOF. Over a mean period of 3.1 years for the pregnancy group and 2.7 years for the comparison group, there was no significant change in the RVEDVi, RVEF, RV mass, pulmonary regurgitation severity, left ventricular (LV) volumes, LV ejection fraction (LVEF), or LV mass when comparing the baseline CMR and the follow-up CMR in either of the groups. There was a slight increase in RV indexed end-systolic volume (RVESVi) when comparing the baseline CMR and the follow-up CMR in the pregnancy group (68.93, SD 23.34 ml/m2 at baseline vs. 72.97, SD 25.24 mL/m2 at follow-up, P = .028). Using a mixed effects model for CMR parameters change over time; when adjusted for time between baseline and follow-up CMR there was no significant difference in rate of change between the pregnancy and comparison groups. Most ventricular remodeling parameters measured by CMR did not significantly change in subjects with rTOF who completed pregnancy or in nulliparous subjects with rTOF. In the pregnancy group, RVESVi is larger in those individuals who have undergone pregnancy without a significant change in ventricular function. These patients should be followed longitudinally to determine the long-term ventricular and clinical effects of pregnancy.